Innovation Project ''Masculine Aroma''(Rose and Cinnamon for Maternity) - NURUL AINI SURIA SAPUTRI (Journal of Public Health Indonesian, 2024)
Labor is the process of opening and thinning the cervix so that the fetus can descend into the birth canal. Labor is divided into four stages, namely labor in stage 1 (opening stage), stage II (fetal expulsion), stage III (uri stage), stage IV (monitoring stage).  The results of the study with the theory that rose flowers are anti-depressants so that they can make the soul calm. To reduce the intensity of pain during the active phase of normal labor primigravida is to give twenty minutes of rose effleurage aromatherapy. Rose aromatherapy is one method that can be used to reduce the cause of pain. The aroma that comes from aromatherapy works to influence a person's emotions with the limbic (through the olfactory system) and the emotional center of the brain.(Tatang, 2016)